Penguatan Moderasi Beragama melalui Peran KUA Perbaungan dalam Menjaga Kerukunan Antar Umat Beragama Masyarakat Perbaungan - Syah Ahmad Qudus Dalimunthe; Mailin Mailin (Al-Balagh : Jurnal Komunikasi Islam, 2023)
Indonesia is a very diverse country. This makes Indonesia vulnerable to inter-ethnic or religious conflicts. To avoid this conflict there must be harmony between religious communities. One of the efforts made by government organizations such as the KUA is to maintain cultural communication so that people and people who live in the community can unite and interact with adherents of other religions. The theory used in this study is the concept of communication and cultural conflict from Samovar and Little John and Dominici. Then also use the concept of the relationship between Gillin and Gillin. The study was conducted through qualitative research, and aimed to explore differences in communication as well as results for residents and the general population of different religions. This investigation has revealed that there is a combination of population. This presentation shows that the interaction between the two religions is mutually beneficial, so there is no conflict as seen in other religions